FOTODEGRADASI ZAT WARNA TEKSTIL CONGO RED DENGAN FOTOKATALIS ZnO-ARANG AKTIF DAN SINAR ULTRAVIOLET (UV) - I Gusti Ayu Adesia Saraswati; Ni Putu Diantariani; Putu Suarya (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
The research was conducted to study photodegradation of congo red textile dyes by using photocatalyst ZnO-activated carbon and UV light. The parameters observed were optimum quantity of the photocatalyst ZnO-activated carbon, optimum pH, optimum radiation time, reaction rate constant, and the effectivity of photodegradation congo red. Photocatalyst ZnO-activated carbon was synthesized using sol-gel method with the ratio of ZnO : activated carbon 5:1. The results showed that the optimum condition of photodegradation congo red required 50 mg of photocatalyst ZnO-activated carbon, pH 4, and 5 hours exposured to UV light radiation. The photodegradation rate constant of congo red using photocatalyst ZnO-activated carbon was 0.1745 hours-1 and without photocatalyst was 0.0200 hours-1. The photocatalyst ZnO-activated carbon in its optimum conditions was effective to reduce congo red textile dyes with 91.81 ± 1.24 percentages of degradation.